Exudate and Propolis from Escallonia Pulverulenta: Phytochemical Characterization and Antibacterial Activity - Echeverria-Morgado, J (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
Propolis is a complex mixture formed from exudates that bees collect from plants and then mix with beeswax and their own salivary enzymes. Chilean propolis is characterized by the presence of phenolic compounds, which are considered responsible for the biological activities. The endemic species Escallonia pulverulenta (Ruiz and Pav.) Pers. [Escalloniaceae] is a recognized source of exudate to produce propolis. This study reports for the first time the chemical profile and antibacterial activity of E. pulverulenta exudate and leaves, as well as two samples of Chilean propolis. Palynological and morphological analysis showed the presence of E. pulverulenta as one of the main species in the propolis samples. UPLC-MS/MS analyses enabled the identification of phenolic acids in the leaves and in the propolis. Conversely, flavonoids are mainly present in exudates and propolis. Quercetin is the most abundant flavonol in the exudate, with similar concentrations in the propolis samples. Nevertheless, the main compound present in both samples of propolis was the flavanone pinocembrin. The antibacterial results obtained for exudate and propolis have shown a similar behavior, especially in the inhibition of Streptococcus pyogenes. These results show the importance of the exudates collected by the bees in the chemical composition and antibacterial capacity of propolis. © 2024 by the authors.
Keywords: Escallonia pulverulenta; leaves; exudate; propolis; phenolic acids; flavonoids; antimicrobial activity